Improving microplastics aggregate settling velocity through ballasted flocculation via natural-based coagulants and nonintrusive image monitoring - Godoy, Luiz Gustavo Rodrigues [UNESP]; de Oliveira, Maria Gabrielle Custodio [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Sharifi, Soroosh; dos Reis, Adriano Gonçalves [UNESP] (Elsevier, 2025)
Microplastics (MPs), which are emerging pollutants with significant potential human health impacts, are found in drinking water from treatment plants. This study investigated the enhancement of polyvinyl chloride (PVC) MP removal through ballasted flocculation via a natural-based coagulant. A “saline extract from Moringa oleifera seeds” (MO) was employed as a natural coagulant, with sodium alginate (SA) used as a bioflocculant and anionic polyacrylamide (PAM) used as a chemical flocculant for comparison. Tests were conducted to compare the performance of ballasted flocculation with that of conventional flocculation (using a natural coagulant alone and with the addition of a flocculant). The settling velocity (vs) of each aggregate was individually monitored via a nonintrusive image technique through particle velocimetry (PIV). Conventional flocculation using only MO resulted in 69.0 % removal under the best conditions, with an average floc size of 63.5 μm and vs of 0.54 cm/min. There was no significant difference between the SA flocculant and PAM in conventional flocculation, with a floc size and vs of 84.0 μm and 0.66 cm/min, respectively. On the other hand, ballasted flocculation via MO and PAM increased both the floc size (100.0 μm) and settling velocity (21.4 cm/min) to values that were 40-fold greater than those of conventional flocculation. This study underscores the potential of ballasted flocculation via natural-based coagulants and flocculants monitored via a nonintrusive image for efficient MP removal during drinking water treatment.